EXTRACTION TECHNIQUES FOR MEDICAL AND AROMATIC AND MODERN INDUSTRIAL PRODUCTION OF FOOD PRODUCTS - Kostić-Nikolić, Slavica (Economics of Agriculture, 2011)
Modern industrial production of food products is characterized by the use of certain additives. The food science, by using the modern diagnostic methods, significantly affects the new findings regarding the harmless or harmfully effect of certain substances. The important trends in food industry production of food products today is implementation of natural ingredients. It is possible to obtain extracts (essential oil) with antioxidant characteristics. The paper points out the importance of certain separation process for isolating natural ingredients from drugs. The aim of this paper is to compare different extraction techniques such as distillation with steam, hydro distillation, the application of classical organic solvents and supercritical extraction (SCFE) in production of essential oil. To obtain these goals, the following works will be carried out: investigate the chemical composition of essential oil, investigate the effects of quality and yield, the selection of the operating conditions depends on the specific compound or compound family to be extracted. There are five crucial parameters that need to be taken into account of essential oils including: extraction temperature, extraction pressure, extraction time, CO2 flow rate and particle size. The SCFE method offers many important advantages over hydro distillation.